HUBUNGAN BEBAN KERJA DAN MANAJEMEN WAKTU TERHADAP KELELAHAN KERJA PADA PERAWAT IGD RUMAH SAKIT HERMINA MAKASSAR - Tenri Diah T.A; Adhinda Putri Pratiwi (Jurnal Kesehatan dan Kedokteran, 2022)
Nurses are professional medical personnel who are always at the forefront of all hospitals and hospital medical services. 91.9% of nurses suffer from fatigue. Work-related fatigue is an important issue that affects caregiver performance and manifests itself as physical and mental fatigue. The survey results from several countries concluded that work accidents accounted for 50% of the incidence of work accidents. The increase in the number of patients during the last two years has caused most nurses to complain of fatigue when working because in addition to the increasing workload and nurses are less able to manage their time so that most nurses experience fatigue when working. The purpose of this study was to examine the relationship between workload and time management on work fatigue in nurses in the emergency room at Hermina Hospital Makassar. The research method used is quantitative with an analytical observation approach. This research was carried out in May-June 2022 and the sample in this study amounted to 60 people who were the total nurses who worked in the emergency room at Hermina Hospital Makassar. The results showed that there was a relationship between workload and work fatigue with a p value of 0.003 <0.05, and there was also a relationship between time management and work fatigue with a p value of 0.001 <0.05